Answer:
[tex]y(x)=3e^{5x}-2xe^{5x}[/tex]
Step-by-step explanation:
The given differential equation is [tex]y''-10y'+25y=0[/tex]
The characteristics equation is given by
[tex]r^2-10r+25=0[/tex]
Finding the values of r
[tex]r^2-5r-5r+25=0\\\\r(r-5)-5(r-5)=0\\\\(r-5)(r-5)=0\\\\r_{1,2}=5[/tex]
We got a repeated roots. Hence, the solution of the differential equation is given by
[tex]y(x)=c_1e^{5x}+c_2xe^{5x}...(i)[/tex]
On differentiating, we get
[tex]y'(x)=5c_1e^{5x}+5c_2xe^{5x}+c_2e^{5x}...(ii)[/tex]
Apply the initial condition y (0)= 3 in equation (i)
[tex]3=c_1e^{0}+0\\\\c_1=3[/tex]
Now, apply the initial condition y' (0)= 13 in equation (ii)
[tex]13=5(3)e^{0}+0+c_2e^{0}\\\\13=15+c_2\\\\c_2=-2[/tex]
Therefore, the solution of the differential equation is
[tex]y(x)=3e^{5x}-2xe^{5x}[/tex]